A Crossed Kana Agraphia - K. Abe; R. Yokoyama; T. Yanagihara (Behavioural Neurology)
We report a right-handed man who developed selective Kana (phonogram) agraphia following an infarct in the non-dominant right cerebral hemisphere. His ability for comprehension, reading and writing of Kanji (ideogram) was unaffected. Kana errors consisted of substitution with another letter and the number of target words was well preserved. The lesion responsible for his Kana agraphia included the right Wernicke's area (the posterior one-third or one-half of the superior temporal gyrus) on MRI, but he did not have aphasia. Based on these findings, we conclude that the language function in some dextral people may be partially lateralized to the right cerebral hemisphere.